2022
DOI: 10.1038/s41598-022-10167-2
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of intravenous sedation using midazolam versus dexmedetomidine in elderly patients with dementia: a randomized cross-over trial

Abstract: Differences between the effects of intravenous sedation with midazolam (MID) and dexmedetomidine (DEX) on the cerebral function of elderly patients with severe dementia are unclear. This study aimed to compare the effects of intravenous sedation with MID or DEX on parameters such as brain waves and cerebral blood flow (CBF). This cross-over study analyzed 12 patients with severe dementia, with each patient receiving both drug treatments. Each drug was administered until a Modified Observer’s Assessment of Aler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Meanwhile, on giving induction inhalation, halothane declines blood pressure on average arteries and saturation oxygen arteries up to 2 times more than Isoflurane. That is, giving anesthesia inhalation, Isoflurane safer for changing hemodynamic than halothane (Morimoto et al, 2022;Shoroghi et al, 2011).…”
Section: Most Surgeries Performed Inmentioning
confidence: 99%
“…Meanwhile, on giving induction inhalation, halothane declines blood pressure on average arteries and saturation oxygen arteries up to 2 times more than Isoflurane. That is, giving anesthesia inhalation, Isoflurane safer for changing hemodynamic than halothane (Morimoto et al, 2022;Shoroghi et al, 2011).…”
Section: Most Surgeries Performed Inmentioning
confidence: 99%
“…Conversely, TOI has been used as a marker of brain oxygenation to investigate therapeutic efficacy with mixed results. Two studies observed negligible TOI reactivity in AD with midazolam administration [14], [15], whereas Viola et al [13] observed significant increases in TOI in AD with brain reperfusion rehabilitation therapy alongside improved MMSE scores. The unclear nature of the alterations in TOI may be due to issues with intra-device variation [16].…”
Section: Resting State Brain Oxygenation Is Reduced In Prodromal Deme...mentioning
confidence: 99%